Expert politicians, electoral control, and fiscal restraints - Uwe Dulleck; Berthold U. Wigger (Center for Economic Studies and ifo Institute (CESifo), 2012)
Fiscal restraints have been argued to force today's governments to internalize the externalities that result from extensive borrowing on future electorates and governments as well as on other countries by causing fiscal instability. In this article we provide an alternative argument for fiscal restraints which is based on an agency perspective on government. A budget maximizing politician is better informed than the electorate about the necessary spending to ensure the states ability to provide services for the economy. In this respect, the politician is an expert in the meaning of the credence good literature. The electorate, being able to observe the budget but not the necessary level of spending, will reelect a government if its budget does not exceed a critical level. A fiscal restraint limits the maximum spending a government will choose if the reelection level is not sufficient to ensure the state's ability to provide services to the economy. We determine when such a fiscal restraint improves voter welfare and discuss the role of the opposition in situations where very high levels of spending are required.
Keywords: D82; H50; H61; 330; electoral control; fiscal restraints; credence goods; Finanzpolitik; Erfahrungsgüter; Verschuldungsrestriktion; Politiker; Wiederwahl; Theorie